A Versatile Electrochemical Biosensor for the Detection of Circulating MicroRNA toward Non‐Small Cell Lung Cancer Diagnosis. Issue 22 (25th March 2022) - Meng, Fanyu; Yu, Wenjun; Chen, Changqiang; Guo, Susu; Tian, Xiaoting; Miao, Yayou; Ma, Lifang; Zhang, Xiao; Yu, Yongchun; Huang, Lin; Qian, Kun; Wang, Jiayi
Abstract: Circulating microRNAs (miRNAs) can be used as noninvasive biomarkers and are also found circulating in body fluids such as blood. Dysregulated miRNA expression is associated with many diseases, including non‐small cell lung cancer (NSCLC), and the miRNA assay is helpful in cancer diagnosis, prognosis, and monitoring. In this work, a versatile electrochemical biosensing system is developed for miRNA detection by DNAzyme‐cleavage cycling amplification and hybridization chain reaction (HCR) amplification. With cleavage by Mn 2+ targeted DNAzyme, DNA‐walker can move along the predesigned DNA tracks and contribute to the transduction and enhancement of signals. For the electrochemical process, the formation of multiple G‐quadruplex‐incorporated long double‐stranded DNA (dsDNA/G‐quadruplex) structures is triggered through HCR amplification. The introduction of G‐quadruplex allows sensitive measurement of miRNA down to 5.68 fM with good specificity. Furthermore, by profiling miRNA in the NSCLC cohort, this designed strategy shows high efficiency (area under the curve (AUC) of 0.879 using receiver operating characteristic (ROC) analysis) with the sensitivity of 80.0% for NSCLC early diagnosis (stage I). For the discrimination of NSCLC and benign disease, the assay displays an AUC of 0.907, superior to six clinically‐acceptable protein tumor markers. Therefore, this platform holds promise in clinical application toward NSCLC diagnosis and prognosis. Abstract : Circulating miRNAs can be used as noninvasive biomarkers for lung cancer (LC) diagnosis. A versatile electrochemical biosensing system is developed for miRNA detection by DNAzyme‐cleavage cycling amplification and hybridization chain reaction amplification. By profiling miRNA in the LC cohort, this designed strategy shows high efficiency and sensitivity for lung tumor early diagnosis and prognosis.